Perceived EWOM: Sebagai Faktor Analisis Dalam Menentukan Kredibilitas dan Pengadopsian eWOM Bagi Wisatawan Pada Forum Diskusi Online Kaskus Subforum OANC dan Travellers - Arif, Mukhamad Sofyan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this study to analyze perceived eWOM as a factor analysis to explain the information that credible and can be adopted for travellers in online discussion forum Kaskus Subforum OANC and Travellers by using the theory of Elaboration Likelihood Model (ELM). The sampling technique used purposive sampling with 100 valid respondents. The analysis tool used Partial Least Square (PLS). This study provides results that eWOM quality has a significant effect and be a strongest predictor influence on eWOM credibility, and also eWOM quantity has a significant effect and be a strongest predictor influence on eWOM adoption. Source credibility has not significant effect to eWOM adoption for travellers, but significant effect to eWOM credibility. The results of this study concluded that the concept of ELM, the central-route as the most influential of eWOM credibility, while these peripheral-route as the most influential of eWOM adoption. This study provides a recommendation for travelers to pay more attention eWOM quality and source credibility as a strong influencer to analyze the credibility of the information, while eWOM quantity as an strong influencer to adopt information.Keyword: Perceived eWOM, eWOM Credibility, eWOM Adoption, Online Review